2019
DOI: 10.1093/ehjci/jez076
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous origin of the coronary artery coursing between the great vessels presenting with a cardiovascular event (J-CONOMALY Registry)

Abstract: Aims Anomalous origin of the coronary artery (AOCA) with an inter-arterial course (IAC) between the great vessels poses a risk for a life-threatening cardiovascular event. We assessed, in a registry-based study, the clinical features, treatment strategies, and prognoses of life-threatening cardiovascular events ensuant to AOCA. Methods and results Included were 65 AOCA patients (48 men/17 women, aged 41 ± 23 years) from 40 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Mainwaring and colleagues 3,12,13) proposed that intramural anatomy is the key risk factor associated with ischemic symptoms and suggested that all intramural coronary arteries should undergo surgical repair. In addition, Nagashima and colleagues 7) reported that age≤40 ages, male sex, participation in sporting activity, absence of prodromal symptoms, acutely angled (≤30°) take-off from the aorta, and absence of luminal narrowing of the inter-arterial course segment were associated with sudden cardiac arrest in patients in AAOCA with inter-arterial course. Take-off angle of the AAOCA from the ascending aorta might be a key factor involved in sudden death (Fig.…”
Section: Surgical Therapy For Anomalous Aortic Origin Of a Coronary Amentioning
confidence: 99%
See 3 more Smart Citations
“…Mainwaring and colleagues 3,12,13) proposed that intramural anatomy is the key risk factor associated with ischemic symptoms and suggested that all intramural coronary arteries should undergo surgical repair. In addition, Nagashima and colleagues 7) reported that age≤40 ages, male sex, participation in sporting activity, absence of prodromal symptoms, acutely angled (≤30°) take-off from the aorta, and absence of luminal narrowing of the inter-arterial course segment were associated with sudden cardiac arrest in patients in AAOCA with inter-arterial course. Take-off angle of the AAOCA from the ascending aorta might be a key factor involved in sudden death (Fig.…”
Section: Surgical Therapy For Anomalous Aortic Origin Of a Coronary Amentioning
confidence: 99%
“…Based on several studies of AAOCA as a frequent cause of sudden cardiac death in young athletes, the main mechanism responsible for ischemic cardiovascular events is presumably incremental mechanical compression of the inter-arterial course by the great vessels or kinking of the sharp angulation at the AAO-CA ostium during exercise [4][5][6][7] . Nagashima and colleagues 7) suggested that the latter mechanism contributes to a greater proportion of ischemic cardiovascular events, based on the findings of their retrospective clinical study. In addition, they noted that coronary spasm might influence cardiovascular events in patients with AAOCA 7) .…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Follow‐up of patients managed surgically or medically in this registry may further help with evidence‐based protocols . In addition, the Japanese Coronary Anomaly Registry suggested patients with age ≤40 years, male sex, sporting activity, and an acute take‐off angle appear to be risk factors for sudden cardiac death and thus surgical intervention may be appropriate therapy …”
mentioning
confidence: 99%